Pengaruh Harga dan kualitas produk Terhadap keputusan pembelian Pada Kopi Ajoe Keliling di kota Padang - Genta Putra; SISKA LUSIA PUTRI SISKA (New Economy, 2026)
This research aims to determine the effect of Price and Product Quality on the Purchasing Decision of Ajoe Coffee in Padang City. The population in this study consists of all consumers of Ajoe Coffee mobile in Padang City, the exact number of which is unknown. A sample of 150 respondents was taken. Data were obtained by distributing questionnaires, which were then processed and tested using IBM SPSS Statistics 22. From the conducted research, it was found that based on the results of hypothesis testing, Price has a positive and significant effect on the Purchasing Decision of Ajoe Coffee in Padang City, Product Quality has a positive and significant effect on the Purchasing Decision of Ajoe Coffee in Padang City, and Price and Product Quality together have a positive and significant effect on the Purchasing Decision of Ajoe Coffee in Padang City.